Performance Evaluation of Hybrid Ground-coupled Heat Pump Indirect Heating Systems. (May 2017) - Li, Hong; Sun, Liangliang
Abstract: This paper proposed two kinds of hybrid ground-coupled heat pump (HGCHP) indirect heating systems (system 1and system 2) for a villa building in Beijing. The numerical simulation of two systems is carried out based on the TRNSYS software. The influences of different operating modes on energy performance are analyzed. And the economic feasibility is discussed using the life cycle cost (LCC) method. The results indicate that system 2 shows better energy performance with the designed solar fraction for DHW (fsol, DHW ) below 80%. When the higher fsol, DHW is feasible, system 1 is preferred. Besides, system 1 shows advantage in keeping the soil temperature constant. In terms of LCC, both systems are better options compared with the conventional GCHP system.